Validation of a moral distress instrument in nurses of primary health care - Priscila Orlandi Barth; Flávia Regina Souza Ramos; Edison Luiz Devos Barlem; Graziele de Lima Dalmolin; Dulcinéia Ghizoni Schneider (Universidade de São Paulo, 2018)
ABSTRACT Objective: to validate an instrument to identify situations that trigger moral distress in relation to intensity and frequency in primary health care nurses. Method: this is a methodological study carried out with 391 nurses of primary health care, applied to the Brazilian Scale of Moral Distress in Nurses with 57 questions. Validation for primary health care was performed through expert committee evaluation, pre-test, factorial analysis, and Cronbach's alpha. Results: there were 46 questions validated divided into six constructs: Health Policies, Working Conditions, Nurse Autonomy, Professional ethics, Disrespect to patient autonomy and Work Overload. The instrument had satisfactory internal consistency, with Cronbach's alpha 0.98 for the instrument, and between 0.96 and 0.88 for the constructs. Conclusion: the instrument is valid and reliable to be used in the identification of the factors that trigger moral distress in primary care nurses, providing subsidies for new research in this field of professional practice.